Desafios e perspectivas de uma abordagem interdisciplinar de ensino na área das ciências da natureza e matemática na formação inicial de professores - Marques, Keiciane Canabarro Drehmer (2020)
This research meets the needs of teacher training regarding the interdisciplinary approach in the context of teaching practices. In view of the lack of interdisciplinary practices in the initial teacher education, a Teaching Project, called Inter-Undergraduate, it was prepared for academics of undergraduate courses in Biology, Physics, Chemistry and Mathematics, with a view to providing these experiences. Thus, in this thesis, we investigate what are the challenges and perspectives in the implementation of this teaching project. We conceived the present work in the methodological perspective of Educational Design Research (PDE), to analyze the proposed solution (Inter-Undergraduate) in order to investigate the delimited problem, which is the lack of interdisciplinary practices in the initial training of teachers in the field of Natural Sciences and Mathematics (CNM).The objective of the study was to elaborate, implement and evaluate this Project, with an interdisciplinary approach for undergraduate students in the area of Natural Sciences and Mathematics, at the Federal University of Santa Maria (UFSM). It is worth mentioning that the undergraduate students in the disciplines already mentioned are part of a federal university in the south of the country. The data sources were the Pedagogical Projects of the Courses, questionnaires, production of the activities of the undergraduate students participating in the project, observations and notes by the researcher. The data set was analyzed from the point of view of a qualitative approach. The development of the project took place between May and December 2018, with face-to-face and distance activities, starting with 50 students and concluding with 27. These activities were carried out in groups and with an interdisciplinary theoretical-practical approach. We identified the challenges faced in the planning and implementation of the project such as: incompatibility of schedules among courses to hold training meetings; capturing and maintaining participants; great variability among semesters of undergraduate students; lack of time for groups to meet and carry out activities; difficulties in interactions with group colleagues and resistance in building interdisciplinary activities. In addition, the groups presented difficulties throughout the project, for example, building interdisciplinary relationships among the curriculum components in the preparation of the proposed tasks. In this sense, the results indicate that interdisciplinary practices are still a challenge in the initial teacher education, but that a way to overcome this would be the incorporation of experiences that work the possible articulations among the curricular components that form the area of Natural Sciences and Mathematics. We hope that the results obtained in the set of investigations for this thesis will prompt new research, new perspectives and reflections on the initial teacher education, with the development of knowledge articulated in an interdisciplinary perspective.